(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Anita Desai and Manju Kapur are the outstanding Indian women writers who speak to the agony and strife of the cutting edge taught women that battle between convention and modernity from one perspective and uniqueness and freedom then again. The women characters in their books decide to battle and challenge the customary and culturally acknowledged standards and flows of society. They are additionally confronting the duties by trying to fit themselves in the socio cultural methods of the changed society. In Anita Desai’s Fire On The Mountain and Manju Kapur’s Difficult Daughters speak to the picture of new woman who battle among convention and innovation to set up her very own character by being economically independent and without relying upon her male partner - be on the father, the husband, the sibling or the child. Anita Desai and Manju Kapur in their books outline the picture of new woman who requests to hold a similar position and status like that of man in the society with equivalent sexuality and rights. They are simply the defiant ladies who look for disclosure, dignity, self-governance and self administer as they are gotten between primitive qualities and the fast approaching new life.